Attitude Dimensions and Shopping Mall Purchasing - Manandhar, Raju Bhai (Management Dynamics, 2020)
The concept of attitude has been one of the main concept used to explain individual differences. The main objective of the study was to examine association between attitude dimensions and shopping mall purchasing and to determine the impact of advertising on shopping mall purchasing in Nepalese consumers. The present study is descriptive and analytical in nature. Structured questionnaire technique under survey approach is applied for collecting primary data with five point Likert scale questionnaire. The population of this study targeted the consumers of shopping malls in Kathmandu valley. This sample size has been derived for unknown population that is 384. The judgment sampling technique has been used in this research to make this study more inclusive and representatives. Descriptive statistics and inferential statistics such as correlation analysis and Regression analysis have been used to analyze the data. The study found that the affection and behavior components are positively associated but cognition is negatively associated with shopping mall purchasing. However the study also found that advertisement has no significant impact on shopping mall purchasing.